Chemicals, Nutrition, and Autism Spectrum Disorder: A Mini-Review - Fujiwara, Takeo; Morisaki, Naho; Honda, Yukiko; Sampei, Makiko; Tani, Yukako (Frontiers in Neuroscience, 2016)
The rapid increase of the prevalence of autism spectrum disorder (ASD) suggests that exposure to chemicals may impact the development of ASD. Therefore, we reviewed literature on the following chemicals, nutrient to investigate their association with ASD: 1) smoke/tobacco, 2) alcohol, 3) air pollution, 4) pesticides, 5) endocrine-disrupting chemicals, 6) heavy metals, 7) micronutrients, 8) fatty acid, and 9) parental obesity as a proxy of accumulation of specific chemicals or nutritional status. Several chemical exposures such as air pollution (e.g., particular matter 2.5), pesticides, bisphenol A, phthalates, mercury, and nutrition deficiency such as folic acid, vitamin D, or fatty acid may possibly be associated with an increased risk of ASD, whereas other traditional risk factors such as smoking/tobacco, alcohol, or polychlorinated biphenyls are less likely to be associated with ASD. Further research is needed to accumulate evidence on the association between chemical exposure and nutrient deficiencies and ASD in various doses and populations.